First records of Leptopezella Sinclair & Cumming (Diptera: Hybotidae: Ocydromiinae) from Brazil - Barros, Luana Machado; Freitas-Silva, Rafael A.p.; Ale-Rocha, Rosaly (Zootaxa, 2019)
Leptopezella Sinclair & Cumming, 2007 is a small genus of Ocydromiinae characterized by the absence of cell dm (Fig. 3) and presence of ventral spine-like setae on the hind first tarsomere (Fig. 2). It was first mentioned as “undescribed genus A” in the key of Sinclair & Cumming (2000) and later described including four species: L. anatolica Sinclair & Cumming, 2007, L. perata Sinclair & Cumming, 2007 and L. spinosa Sinclair & Cumming, 2007 from Australia and L. masneri Sinclair & Cumming, 2007 from Bolivia (Sinclair & Cumming 2007). In South America the genus has been recorded so far from Bolivia and Argentina (Sinclair & Cumming 2000, 2007). In the present study we record the genus occurring for the first time in several administrative states from Brazil.